Molecular profile of the Lynch Syndrome in the Republic of Macedonia - Marija Hiljadnikova-Bajro; Toni Josifovski; Milco Panovski; Aleksandar J. Dimovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
The most frequent type of hereditary colorectal cancer, the one occurring in the setting of the Lynch syndrome (LS) is considered a phenotypic manifestation of a germline defect in the mismatch repair mechanism i.e. in the MLH1, MSH2, MSH6 or PMS2 gene. Aiming towards establishment of a standardized protocol involving molecular analyses for diagnosis of this syndrome and developing a unique national register of families with hereditary colorectal cancer syndromes in the Republic of Macedonia, we began a prospective study to reveal the genetic defects among Macedonian patients with colorectal cancer (CRC) and identifying families with hereditary CRC. A total of 53 patients fulfilling the revised Bethesda criteria for MSI-genetic testing were compared to 350 patients with sporadic CRC. The results reveal significant differences in age at diagnosis (p=0.03), involvement of microsatellite instability (p<0.0001) and localization of the tumor in respect to flexura lienalis (p=0.009) and suggest affiliation of the majority of the "Bethesda+" CRCs to the so called Familial Colorectal cancer Type X group. The molecular characterization of LS suspects identified the novel MLH1 c.392C>G nonsense mutation with a possible founder effect in the Macedonian population, the MLH1 ex.3-12 deletion, as well as the c.244A>G mutation, IVS14- 19A>G and IVS4+65A>C changes in MLH1 without confirmed pathological significance. The observed high frequency (87.5%) of the Ile219Val (c.655A>G) variant in MLH1 among the LS suspects prompts further analyses to evaluate its involvement in the development of hereditary CRC by itself or as a risk modifying factor among the patients from the Republic of Macedonia.